FENOMENA PEMAKAIAN PRONOMINA (DHOMIR) ANTUM SEBAGAI REPRESENTASI PRINSIP KESANTUNAN DI PONDOK MODERN AN-NAJAH CINDAI ALUS PUTRI - Azhar, Restuwati (MIMESIS, 2021)
This study was conducted in order to 1) describe the use of pronoun ‘antum’ by students in daily basis interactions, and 2) describe the relationship between the use of the pronoun ‘antum’ and the principle of politeness. The data in this study were obtained through the method of participants observations and the distribution of questionnaires containing questions with open answers pattern. The results of the analysis have indicated that the pronoun ‘antum’ is used by students as a pronoun that refers to the second person for the plural male, for the elder person, and for the person who is respected. In addition, the use of the pronoun ‘antum’ is a way of showing respect for older person or respected speech partners, and is considered as a form of ‘costumized’ politeness.